Multiple Linear Regression Model of Determinants of the Livestock and Fishery Sub-sectors' Contribution in Mandailing Natal Regency - Aswan, Novita; Widiasyih, Anugrah Sri; Fadhillah, Yusra; Pulungan, Sutan; Hasanah, Wida Khoirul; Yusditara, Wisnu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
This study aims to analyze the determinant factors influencing the contribution of livestock and fisheries subsectors to the economy of Mandailing Natal Regency using a multiple linear regression model with a quantitative-mathematical approach. The study employs secondary time series data from 2015-2024 obtained from the Central Bureau of Statistics (BPS). The dependent variables are the Gross Regional Domestic Product (GRDP) of livestock and fisheries subsectors, while the independent variables include livestock population, meat production, egg production, capture fisheries production, aquaculture production, and number of fishery households. Mathematical analysis was conducted through two regression models with classical assumption testing (normality, multicollinearity, heteroscedasticity, and autocorrelation) to ensure the Best Linear Unbiased Estimator (BLUE) properties. The results show that the regression models have excellent predictive capability with R2 values of 0.994 for livestock and 0.997 for fisheries. Livestock population is the dominant determinant for the livestock subsector (β=0,852;p<0.01), while capture fisheries production is the dominant determinant for the fisheries subsector (β=0,789; p<0.01).